2011
DOI: 10.1111/j.1467-789x.2010.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geographic life environments on cardiometabolic risk factors: a systematic review, a methodological assessment and a research agenda

Abstract: Recent environmental changes play a role in the dramatic increase in the prevalence of cardiometabolic risk factors (CMRFs) such as obesity, hypertension, type 2 diabetes, dyslipidemias and the metabolic syndrome in industrialized countries. Therefore, identifying environmental characteristics that are associated with risk factors is critical to develop more effective public health interventions. We conducted a systematic review of the literature investigating relationships between characteristics of geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
318
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(339 citation statements)
references
References 70 publications
11
318
2
2
Order By: Relevance
“…[7][8][9] Neighborhoods with poor community-level or government economic resources often have fewer resources related to the built environment, including poor recreational facilities, supermarkets, lack of functioning sidewalks, and limited access to parksall factors that may contribute to obesity. 10 In addition, neighborhood poverty also correlates with poor social environments, including higher crime rates, low aesthetic quality, poor social cohesion and social capital, and increased residential segregation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Neighborhoods with poor community-level or government economic resources often have fewer resources related to the built environment, including poor recreational facilities, supermarkets, lack of functioning sidewalks, and limited access to parksall factors that may contribute to obesity. 10 In addition, neighborhood poverty also correlates with poor social environments, including higher crime rates, low aesthetic quality, poor social cohesion and social capital, and increased residential segregation.…”
Section: Introductionmentioning
confidence: 99%
“…This mirrors the broader literature that has examined associations between the built environment and obesity. Recent systematic reviews [16][17][18] concluded that generalizing across studies is not possible. In response, focus has shifted to disparities in quality and condition of parks in addition to their availability and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The patient's home neighbourhood will be used as a surrogate for patient characteristics, because previous literature shows an association between home neighbourhood and cardiac risk factors, unhealthy behaviours, and overall health. [33][34][35][36][37][38][39][40][41][42][43][44][45] The neighbourhood factors of the arrest location (i.e., the pickup address) will be used to study the effects on bystander CPR, because the emergency response (i.e., bystanders and EMS/paramedics) is contingent on the arrest location. [10][11][12][13][46][47][48] A patient's home address is recorded as mailing address with street name, street number, and postal code, whereas the pickup address is recorded as a mailing address, with latitude and longitude coordinates and a Universal Transverse Mercator (UTM) value.…”
Section: Geocodingmentioning
confidence: 99%